External fixation versus plating in intra-articular distal end radius fractures - Anant, Shubham; Agarwal, Saumya; Gupta, Sanjay; Lal, Anuj Kumar (International Journal of Research in Orthopaedics, 2019)
Background: Distal end radius fractures are one of the most common encountered fractures in Orthopaedics. Prompt intervention in terms of volar locking plate or external fixation can be performed. The purpose of this study was to derive a better outcome as to which type of fixation is a better choice for the treatment of intra-articular distal end radius fracture. Methods: A prospective randomized controlled study was conducted with 30 patients and comparison was made between the plating and external fixator group using the modified clinical-scoring system of Green and O’Brien and demerit point system at each follow-up. Results: In the plating group 14 patient’s fracture united in 6th week and 1 patient’s fracture united at 8th week this result was similar to the external fixator group were 14 patient’s fracture united in 6th week and 1 patient’s fracture united at 8th week. 1 patient each developed wrist joint stiffness and delayed union in the plating group as compared to the external fixator group were 1 patient each developed wrist joint stiffness, delayed union and broken implant in situ and pin tract infection. Conclusions: During the initial follow ups the functional outcome of the plating group were better than the external fixator group but as the time passed at the final follow up plating was only marginally better than the external fixator group. It was seen that radiologically plating lead to a better correction of all the parameters as compared to external fixator group.